Refracted: Alias Grace Series Through a Freudian Perspective - Paiva, Bárbara J. (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2021)
From 1843 to 1872, Grace Marks (Sarah Gadon) served time, at the Kingston Penitentiary, for murdering her employer Thomas Kinnear (Paul Gross), and his housekeeper/lover, Nancy Montgomery (Anna Paquin). In 1859, a young American psychiatric doctor, Dr. Simon Jordan (Edward Holcroft), travels to Kingston, under the request of a clemency committee, to study Grace, helping her restore her lost memory of the crimes, with the purpose of writing a favourable report which would concede Grace‟s pardon. This article undertakes the examination of the television miniseries Alias Grace, based on the 1996 homonymous novel by Canadian author Margaret Atwood, by focusing on the analyses of the overall series through a Freudian perspective. It will be argued that each episode is imbued of symbolism that normally escapes the understanding of the viewer. Therefore, I shall illustrate certain aspects connected with Freudian symbolism, according to film studies language, while establishing other important connections to prove the profuse presence of the male gaze and how Grace Marks, an ambivalent protagonist with a fluid personality, navigates this stereotyped 19th society dominated by patriarchal values and invested in the annihilation of the female subject.